Increased risk of early-onset preeclampsia in pregnant women with COVID-19. (31st December 2023) - Mahajan, Niraj N.; Kesarwani, Shweta; Kumbhar, Padmaja; Kuppusamy, Periyasamy; Pophalkar, Madhura; Thamke, Pratiksha; Asawa, Ruchi; Sharan, Saumya; Mahale, Smita D; Gajbhiye, Rahul K
ABSTRACT: Objective: To estimate incidence, risk of early and late-onset preeclampsia (PE) and understand their relationship with severity of COVID-19. Methods: Pregnant women with COVID-19 (n = 1929) were enrolled from 1 April 2020 to 24 February 2022. Primary outcome measure was incidence and risk of early onset PE in women with COVID-19. Results: The incidence of early and late-onset PE was 11.4% and 5.6%. Moderate to severe COVID-19 was associated with eight times higher risk of early onset PE [aOR = 8.13 (1.56–42.46), p  = 0.0129] compared to asymptomatic group. Conclusions: Risk of early onset PE was higher in pregnant women with symptomatic COVID-19 as compared to asymptomatic women.